2014
DOI: 10.4038/kjm.v2i1.6543
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Perceived Desirability and Perceived Feasibility on Entrepreneurial Intention among Undergraduate Students in Sri Lanka: An Extended Model

Abstract: Particularly, at the outset the researcher writes that, the insight of conducting and model specification for the study was gained from, Guerrero, Rialp, & Urbano, (2006). Due to the proven validity of intention based models to assess entrepreneurial intention and the non-validity of assessing entrepreneurial intention based on psychological characteristics, general dispositions, and personality traits and demographic factors, the researcher investigates the most appropriate model specification to assess entre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 19 publications
3
23
0
1
Order By: Relevance
“…The findings against prior studies demonstrated the Shapero's model (Ngugi et al, 2012) or at least perceived feasibility and perceived desirability (Byabashaija & Katono, 2011;Dissanayake, 2013;Drennan, Kennedy, & Renfrow, 2005;Sajjad, Shafi, & Dad, 2012;Weerakoon & Gunatissa, 2014). However, this finding supported the previous researches conducted by AlHaj et al (2011), Garba, Kabir, and Nalado (2014), and Guerrero, Rialp, and Urbano (2008).…”
Section: Criteriasupporting
confidence: 45%
“…The findings against prior studies demonstrated the Shapero's model (Ngugi et al, 2012) or at least perceived feasibility and perceived desirability (Byabashaija & Katono, 2011;Dissanayake, 2013;Drennan, Kennedy, & Renfrow, 2005;Sajjad, Shafi, & Dad, 2012;Weerakoon & Gunatissa, 2014). However, this finding supported the previous researches conducted by AlHaj et al (2011), Garba, Kabir, and Nalado (2014), and Guerrero, Rialp, and Urbano (2008).…”
Section: Criteriasupporting
confidence: 45%
“…2.2 Entrepreneurial self-efficacy and entrepreneurial intention Entrepreneurial self-efficacy is an individual's capability or capacity to mobilize the motivation, cognitive resources and certain course of action in requisite to achieve success while performing any specific task (Dissanayake, 2013). The belief in one's capability is selfefficacy (Bandura, 2000).…”
Section: Entrepreneurial Intentionmentioning
confidence: 99%
“…Essential psychological capital ingredients, for those who would be entrepreneurs, include self-efficacy, optimism, hope and resilience (Wernsing, 2014). The positive effect of self-efficacy (perceived behavioral control) on EI is well documented (Bae et al , 2014; Dissanayake, 2013; Solesvik, 2017). Previous studies have also reported a strong positive correlation between attitude and intention (Byabashaija and Katono, 2011; Schwarz et al , 2009).…”
Section: Introductionmentioning
confidence: 98%